Analysis of Educational Leadership Theories and Practices in Abu Dhabi Schools - Al Hajeri, Ali (2024)
During the last decade, the UAE education system has undergone many reforms to align its outcomes with requirements of the knowledge-based economy adopted by the UAE government. The Abu Dhabi 2030 vision has emphasized on the role of education as a key contributor to youth development and economy growth. Educational leadership plays a vital role in the success and effectiveness of educational institutions. Effective leadership has been linked to various positive outcomes including enhanced students’ achievement, improved teacher commitment and overall school performance. There has been a substantial investment in Abu Dhabi educational infrastructure, curriculum updating and professional development for educators. These efforts aim to ensure that the students are equipped with the relevant knowledge and skills to succeed in the era of globalization. Despite the considerable improvements in the education system, there is still an important gap in literature concerning the leadership styles practiced in Abu Dhabi schools. While many studies have examined the educational leadership in various global contexts, the specific socio-cultural and economic land scape of Abu Dhabi educational institutions necessities a more focussed investigation. Moreover, the existing studies on educational leadership in Abu Dhabi have been focussing on fragmented and isolated aspects of leadership rather than providing a comprehensive synthesis of the educational leadership practices adopted in Abu Dhabi. This study has adopted a meta-synthesis approach to analyse and understand the educational leadership theories and practices prevailing in Abu Dhabi education institutions based on the previous research studies on the topic. The findings of this study reveal that transformational leadership style is predominant in Abu Dhabi schools displaying many positive impacts in terms of teachers’ satisfaction, students’ achievement and overall school performance. The study also highlighted the diversified, dynamic and evolving nature of Abu Dhabi educational system which necessitates leadership with a high degree of adaptability and exhibition of emotional and cultural intelligence attributes. Furthermore, the study has identified some of the best leadership practices which include the fostering of continuous professional development culture and the promoting collaborative leadership. The gender dimension was also explored, and the findings show that female leaders have been successful as school leaders. Finally, some recommendations were given in the perspective to explore this crucial topic and to expand the research to all the emirates in order to get a comprehensive picture of the educational leadership situation within UAE schools.